A 28 GHz high efficiency fully integrated 0.18 µm combined CMOS power amplifier using power divider technique for 5G millimeter-wave applications - A. F. Hasan; S. A. Z. Murad; F. A. Bakar; T. Z. A. Zulkifli (Institute of Advanced Engineering and Science, 2020)
A 28 GHz power amplifier (PA) using CMOS 0.18 µm Silterra process technology for milimeter wave applications is reported. Maximizing the power added efficiency (PAE) and output power are achieved by optimize the circuit with power divider and cascade configuration. In addition, reverse body bias is also employed for realizing excellent PAE and power consumption. A three stage CMOS PA with power combiner is designed and simulated. The simulation results show that the proposed PA consumes 62.56 mW and power gain (S21) of 8.08 dB is achieved at 28 GHz. The PA achieves saturated power (Psat) of 12.62 dBm and maximum PAE of 23.74% with output 1-dB compression point (OP1dB) 10.85 dBm. These results demonstrate the proposed power amplifier architecture is suitable for 5G applications.